2022
DOI: 10.3390/agronomy12071495
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Effect of an Enhanced Attapulgite for the Control of Four Stored-Product Beetle Species

Abstract: We examined the insecticidal effect of three different dust formulations, which were attapulgite (W), attapulgite mix with oregano essential oil with 52% carvacrol (D1), and attapulgite mix with oregano essential oil with 75% carvacrol (D2), in four major stored-product beetle species, Sitophilus oryzae (L.), Tribolium confusum Jacquelin du Val, Rhyzopertha dominica (F.), and Trogoderma granarium Everts. Sitophilus oryzae was the most susceptible at all three formulations, followed by T. confusum and R. domini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The combined action of plant derivatives with chemical or natural insecticides in order to enhance the insecticidal efficacy against stored product insects has been extensively studied [53][54][55][56][57][58][59][60][61][62]. For instance, Yang et al [56] found that the combined application of the essential oil of Allium sativum L. (Asparagales: Amaryllidaceae) with diatomaceous earth against S. oryzae and the confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae), was significantly more effective than the single application of either the essential oil or the diatomaceous earth.…”
Section: Discussionmentioning
confidence: 99%
“…The combined action of plant derivatives with chemical or natural insecticides in order to enhance the insecticidal efficacy against stored product insects has been extensively studied [53][54][55][56][57][58][59][60][61][62]. For instance, Yang et al [56] found that the combined application of the essential oil of Allium sativum L. (Asparagales: Amaryllidaceae) with diatomaceous earth against S. oryzae and the confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae), was significantly more effective than the single application of either the essential oil or the diatomaceous earth.…”
Section: Discussionmentioning
confidence: 99%
“…Inert dusts are promising alternatives to conventional insecticides against numerous stored-product pests [11,[15][16][17][18][19][20][21][22]. According to their chemical and physical composition, they are divided into several categories, such as (a) zeolite [22][23][24]; (b) attapulgite [20]; (c) graphene [21]; (d) wood ash [17]; and (e) diatomaceous earth (DE) [25][26][27][28][29][30][31]. One of the well-studied categories is diatomaceous earth, which is registered for direct application on grains in many parts of the world [30].…”
Section: Introductionmentioning
confidence: 99%